New Challenges for the Organic Farmers in India – Tourism, Spices and Herbs - Firmino, Ana (Journal for Geography, 2010)
Organic Farming can offer the Indian farmers the possibility to get an added value to their products. Those operating in the Ponda region/Goa benefit from an historical background and highly preserved biodiversity that may entitle them in the future for a GIAHS (Globally Important Agricultural Heritage Systems) project which will prevent these scenic landscapes to be destroyed. The spice plantations are a live Natural Sciences and History lesson for everybody and an attraction for the tourists who find here a pleasant environment, rich flora and fauna, rural tourism, ayurvedic medical care and an array of leisure activities in contact with Nature.